ALK-rearranged lung squamous cell carcinoma responding to alectinib: a case report and review of the literature - Mamesaya, Nobuaki (BMC Cancer, 2017)
BACKGROUND: Although anaplastic lymphoma kinase (ALK) fusion genes are generally identified in lung adenocarcinoma patients, they are relatively rare in patients with squamous cell carcinoma (SqCC). Metastatic ALK-rearranged lung adenocarcinoma patients treated with ALK inhibitors demonstrate higher response rates, improved progression-free survival, and reduced toxicity relative to those treated with conventional chemotherapy regimens. However, the efficacy of treatment with ALK inhibitors in patients with ALK-rearranged lung SqCC remains unknown. CASE PRESENTATION: We discuss a 52-year-old Japanese-Brazilian woman without a history of smoking who was referred to our hospital for evaluation of severe left back pain and a left hilar mass observed on a chest radiograph. The patient was eventually diagnosed on the basis of computed tomography, pathological, and immunohistochemical findings as having Stage IV lung SqCC. First-line treatment with palliative radiotherapy and systemic chemotherapy with cisplatin plus vinorelbine was administered, but was not effective. ALK testing was subsequently performed, revealing positive ALK expression and gene rearrangement. Alectinib therapy was then initiated, which resulted in a gradual, but substantial reduction in tumor size. CONCLUSIONS: To the best of our knowledge, this is the first case report to discuss the successful management of ALK-rearranged lung SqCC with alectinib. We propose that molecular testing for driver mutations should be considered in young patients with a light or no smoking history, even if the histological findings correspond with SqCC, and alectinib therapy represents a reasonable option in cases of ALK-rearranged lung SqCC.